2005
DOI: 10.1097/01.brs.0000169449.68870.f8
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cobb Angle Measurements Using Reformatted Computerized Tomography Scans

Abstract: Reformatted CT images may be used for manual measurement of coronal Cobb angles in idiopathic scoliosis with similar variability to manual measurement of plain radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…It must be borne in mind, however, that the variability in the measurement of Cobb angle itself is considerable, inter- Fig. 8 Distribution of lateral asymmetry curves for the first 168 patients rater variability ranging from 5°to 10° [2,23]. The relationship between ISIS2 lateral asymmetry and radiographic Cobb angle will be limited for patients who are extremely obese or have heavy musculature because identifying the bony landmarks for marking will be more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be borne in mind, however, that the variability in the measurement of Cobb angle itself is considerable, inter- Fig. 8 Distribution of lateral asymmetry curves for the first 168 patients rater variability ranging from 5°to 10° [2,23]. The relationship between ISIS2 lateral asymmetry and radiographic Cobb angle will be limited for patients who are extremely obese or have heavy musculature because identifying the bony landmarks for marking will be more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the rib hump is often more important to the patient than the radiological position of the spine and yet is not measured in standard radiographs. Third, there is considerable variability in the measurement of Cobb angle itself, inter-rater variability ranging from 5°to 10° [2,23]. The availability of low-cost, radiation-free equipment to measure back topography is therefore a key element for decision making by both surgeon and patient.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual average improvement in the Cobb angle was -0.67°in the Pro exercise therapy SEAS and ?1.38°in the PT group. These changes are far too small to be conclusive because the reported error rate in measurement of Cobb angle ranges from 1.7°to 6.5° [21][22][23]. The choice of treatment was left to the patients whose compliance over the 6-12 month period was not assessed nor was there any mention of which criteria were used to prescribe a brace.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact method used to measure the Cobb angle was not described and a nonstandardised method was used in one study [36]. Most studies reported on ''significant'' changes in the Cobb angle which were actually of small magnitude and failed to take into account that the reported error rate in measurement is between 1.7°and 6.5° [21][22][23]. Two studies [17,30] reported on Moire fringe topography, which has been shown to be inaccurate in detecting small changes in curve dimensions [32].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the Cobb angle is then dependant on manually marking reference points on the radiograph to measure against and this will be slightly different on every occasion. The error for Cobb measurement is reported as between 3°and 9° [2][3][4][5]. Thus a change in Cobb angle \ 3°cannot be accepted as a true change as it is within the accepted margins of error.…”
mentioning
confidence: 99%